RANCANG BANGUN APLIKASI MOBILE LEARNING BERBASIS J2ME UNTUK MATA PELAJARAN MATEMATIKA( MOBILE APPLICATION DESIGN BASED LEARNING J2ME FOR SUBJECT MATH ) - Tito Sugiharto (NUANSA INFORMATIKA, 2012)
This study is intended to produce a supplementary learning media for students in High School Mathematics for Mobile-Learning Application form. Target research to be achieved is the media to learn additional attractive and easy to use so as to enhance the learning and achievement of students in mathematics subjects.This research will explore how to design and develop applications based on J2ME Mobile Learning for Mathematics in order to run well on different mobile phones. This application was created to enable users to access a material / substance use mathematics Mobile Learning through mobile applications.Mobile Learning Application is an application J2ME-based alternative learning media independent and can be implemented on mobile phones that support java based CLDC 1.0 and MIDP 2.0.Keywords : Aplikasi Mobile Learning, Matematika , J2ME, Handphone, Learning Media